2021
DOI: 10.36021/jethe.v4i1.156
|View full text |Cite
|
Sign up to set email alerts
|

Teacher-Centered versus Student-Centered Teaching

Abstract: This empirical study examined preferences between teacher-centered and student-centered teaching methods and academic major with 507 undergraduate college students. Surveys were administered to the students that assessed their level of agreement with teaching methods utilized in the classroom. The results indicate that across all academic majors, students’ preferences included a mix of teacher-centered and student-centered approaches, some of which include lecture with student interaction, demonstrations and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 30 publications
0
23
1
3
Order By: Relevance
“…These psychological problems do not only have concrete existence in governmental schools but also o private ones in addition to Saudi governmental and private universities. Even when the researchers set their Saudi subjects into experimental and control groups to solve these psychological problems, the effect of any given treatment was provisional (Oreopoulos, 1993;Nazari, 2019;Murphy, Eduljee, & Croteau, 2021). The Saudi university students have their ideal L2 self, a modal of language professionalism that they try to attain.…”
Section: Research Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…These psychological problems do not only have concrete existence in governmental schools but also o private ones in addition to Saudi governmental and private universities. Even when the researchers set their Saudi subjects into experimental and control groups to solve these psychological problems, the effect of any given treatment was provisional (Oreopoulos, 1993;Nazari, 2019;Murphy, Eduljee, & Croteau, 2021). The Saudi university students have their ideal L2 self, a modal of language professionalism that they try to attain.…”
Section: Research Problemmentioning
confidence: 99%
“…The research studies in the fields of teaching, learning, applied linguistics, positive psychology, and psycholinguistics have seen a significant change from teacher-centered to student-centered education (Murphy, Eduljee, & Croteau, 2021). More focus has been placed on learning and learners rather than instruction and instructors (Noriega, Bonet, & Heppell, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the less visible role of facilitators that the teachers assume in a learner-centred approach, in a teacher-centred approach the teacher acts as the authority figure who transmits knowledge and information, actively managing every aspect of classroom experience, while students passively receive the information (Brown 2014;Lightweis, 2013). In such an instructional setup, the learners have fewer opportunities to interact amongst themselves and practice using the foreign language (Murphy et al 2021), with some authors even suggesting that this approach in fact prevents students' educational development (Duckworth 2009).…”
Section: Hofstede's Individualism/collectivismmentioning
confidence: 99%
“…However, several authors emphasize that redirecting these priorities in the classroom, changing the educational goal, and conceiving of specific knowledge as a means toward that goal and not as an end in itself, requires a genuine change in mentality and teaching practices ( Hong, 2012 ; Murphy et al, 2021 ; Tahirsylaj and Fazliu, 2021 ) or, if we prefer, a genuine conceptual change ( Pozo et al, 2006 ; Ajayi, 2013 ), that is difficult to achieve. Indeed, several studies conducted prior to the pandemic found there was a gap between what teachers prefer and what they really do, as shown by the outcomes of the TALIS project ( OECD, 2009 ; Berger et al, 2018 ), that is, between their conceptions and their practices.…”
Section: Introductionmentioning
confidence: 99%